Nanoparticle-Integrated Hydrogels for Rheumatoid Arthritis: Smart Drug Delivery Strategies for Targeted Therapy and Joint Regeneration - Deepa Joseph; R. Srinivasan (Current Nanomedicine, 2026)
Introduction: Rheumatoid arthritis (RA) is a chronic autoimmune disease character-ized by joint inflammation, synovial hyperplasia, and cartilage degradation. Conventional sys-temic therapies often lead to off-target effects and inadequate drug concentrations at the disease site. Nanoparticle-integrated hydrogels have emerged as promising platforms for localized and sustained drug delivery in RA treatment. Methods: This review summarizes recent advances (2020-2024) in the design of stimuli-responsive nanoparticle-loaded hydrogels for intra-articular RA therapy. Literature was sourced from PubMed, Scopus, and Web of Science using terms such as “nanoparticle hydrogel,” “RA drug delivery,” and “stimuli-responsive.” Articles were screened for novelty, in vivo validation, and mechanistic insight. Results: Various polymers (e.g., chitosan, PEG, hyaluronic acid) and nanoparticles (e.g., PLGA, liposomes, AuNPs, CeO₂) have been integrated into hydrogels to enhance site-specific drug re-lease. Mechanisms include pH-triggered swelling, ROS-labile bond cleavage, and MMP-responsive degradation. Case studies showed 50-60% reductions in TNF-α and IL-6 levels and improved joint histology in CIA models. Three-dimensional (3D)-printed hydrogels and photo-thermal systems further enhance precision targeting and retention. Discussion: Stimuli-responsive hydrogels offer programmable, biocompatible, and minimally invasive treatment strategies. Nanoparticle integration enhances the therapeutic index by improv-ing joint retention, reducing systemic exposure, and enabling real-time control. Challenges re-main in scalability, regulatory clearance, and long-term biocompatibility. Conclusion: Nanoparticle-integrated hydrogels represent a next-generation solution for localized RA therapy, offering controlled release, inflammation targeting, and reduced toxicity. Further preclinical and translational studies are warranted to support clinical adoption.